2020
DOI: 10.1101/2020.10.08.331645
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 elicits robust adaptive immune responses regardless of disease severity

Abstract: The SARS-CoV-2 pandemic currently prevails worldwide. To understand the immunological signature of SARS-CoV-2 infections and aid the search for treatments and vaccines, comprehensive characterization of adaptive immune responses towards SARS-CoV-2 is needed. We investigated the breadth and potency of antibody-, and T-cell immune responses, in 203 recovered SARS-CoV-2 infected patients who presented with asymptomatic to severe infections. We report very broad serological profiles with cross-reactivity to other … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
4
9
0
Order By: Relevance
“…Some specific epitopes are highlighted as being immunodominant in multiple studies. For example, in the context of the HLA-A*02:01 class I molecule, which is the most studied for CD8 SARS-CoV-2 responses, the S 269-277 epitope (sequence YLQPRTFLL) is detected in 81% of HLA-A2+ individuals in the Nielsen study (Nielsen et al, 2020). The same A2 dominant epitope is also reported by Shomuradova et al, who tested 13 A2 peptides in total, and also identified a less strongly recognized epitope (Shomuradova et al, 2020).…”
Section: Immunodominance At the Level Of Specific Epitopes And Allelessupporting
confidence: 80%
See 3 more Smart Citations
“…Some specific epitopes are highlighted as being immunodominant in multiple studies. For example, in the context of the HLA-A*02:01 class I molecule, which is the most studied for CD8 SARS-CoV-2 responses, the S 269-277 epitope (sequence YLQPRTFLL) is detected in 81% of HLA-A2+ individuals in the Nielsen study (Nielsen et al, 2020). The same A2 dominant epitope is also reported by Shomuradova et al, who tested 13 A2 peptides in total, and also identified a less strongly recognized epitope (Shomuradova et al, 2020).…”
Section: Immunodominance At the Level Of Specific Epitopes And Allelessupporting
confidence: 80%
“…This breadth of response is apparently at variance with other reports describing only a limited number of epitopes for SARS-COV-2 (Chen et al, 2021;Le Bert et al, 2020;Lee et al, 2020;Nielsen et al, 2020;Rha et al, 2021;Sekine et al, 2020;Kared et al, 2021;Sahin et al, 2020). In some cases, in vitro expansion with artificial antigens has been utilized, and/or a limited number of subjects, cells, and/or epitope candidates were screened.…”
Section: Breadth Of the T Cell Repertoirementioning
confidence: 69%
See 2 more Smart Citations
“…Habel et al 25 Figure 2B T cell epitopes from convalescent COVID-19 patients Hu et al 31 Table 1 T cell epitopes from convalescent COVID-19 patients Nielsen et al 21 Figure 5B T cell epitopes from convalescent COVID-19 patients Tarke et al 36 Tables S3 and S5 T cell epitopes from convalescent COVID-19 patients Sekine et al 23 Table S2 T cell epitopes from convalescent COVID-19 patients Saini et al 14 Table S5 T cell epitopes from convalescent COVID-19 patients Lee et al 34 Figure 13 T cell epitopes from convalescent COVID-19 patients Rha et al 28 Figure 1C T cell epitopes from convalescent COVID-19 patients Lineburg et al 33 Table S3 T cell epitopes from convalescent COVID-19 patients Nguyen et al 24 Figure 3C Response…”
Section: Star+methodsmentioning
confidence: 99%